Monitoring of chloride and Friedel's salt, hydration components, and porosity in high-performance concrete. (December 2022) - Bachtiar, Erniati; Rachim, Fatmawaty; Makbul, Ritnawati; Tata, Arbain; Irfan-Ul-Hassan, Muhammad; Kırgız, Mehmet Serkan; Syarif, Muhammad; de Sousa Galdino, André Gustavo; Khitab, Anwar; Benjeddou, Omrane; Kolovos, Konstantinos G.; Ledesma, Enrique Fernandez; et al.
Abstract: The innovative paper evaluated the water of the sea as a curing component and mixing constituent in high-performance concrete (HPC). This motivation would provide an understanding for the reader of how the water from the sea affects the HPC. This paper would provide information about the mechanism and the influence of prepared high-performance concrete mixed with either freshwater or seawater and made to cure in freshwater, seawater, or air. The mechanism and the influence were evaluated by XRD tests, SEM observations, and petrography analysis of HPCs at 3 days, 7 days, 28 days, and 90 days. The structure of the Friedel's salt increases tobermorite and ettringite (3CaO.Al2 O3 .3CaSO4 32H2 O) and retards portlandite (Ca(OH)2 ) and calcium silicates (2CaO.SiO2 and 3CaO.SiO2 ) in HPC mixed with seawater for 3–90 days. Air curing reduces the formation of portlandite (Ca(OH)2 ), tobermorite (3CaO.2SiO2 .3H2 O), ettringite (3CaO.Al2 O3 .3CaSO4 32H2 O), and calcium silicate (3CaO.SiO2 ) in seawater HPC while increasing the formation of calcium silicate (2CaO.SiO2 ). SEM analysis supports the mechanism and influence of mixing of seawater, curing in the water of the sea, and curing treatment in the air. According to data from petrographic analysis and porosity testing, the porosity was decreased by the seawater and curing treatment in the seawater in HPC mixes. In terms of hydration components, SEM observation, porosity, and petrographic analysis, the HPC-3 shows the best performance in the work.